2011
DOI: 10.3171/2010.10.peds1057
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic syrinx in the pediatric population: a combined center experience

Abstract: Object Discovery of a syrinx in a child, without a readily identifiable proximate cause such as a Chiari malformation, tumor, or site of tethering, is often a cause of concern for families and a source of consternation for clinicians. There is a paucity of data describing the natural history of an idiopathic syrinx in the pediatric population. The authors present the combined data of 2 major pediatric neurosurgical centers to describe their experience with this condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 9 publications
3
41
0
Order By: Relevance
“…In particular, a nonoperative approach is justified when a patient is either asymptomatic or experiences relatively mild symptoms. In their study on IS, Magge et al 26 also suggested that surgical management of the syrinx may not offer much utility since both their surgical cases either worsened or showed no changes clinically. We routinely may obtain follow-up MR images on an annual basis or more frequently as dictated by symptoms.…”
Section: Presentationmentioning
confidence: 99%
See 3 more Smart Citations
“…In particular, a nonoperative approach is justified when a patient is either asymptomatic or experiences relatively mild symptoms. In their study on IS, Magge et al 26 also suggested that surgical management of the syrinx may not offer much utility since both their surgical cases either worsened or showed no changes clinically. We routinely may obtain follow-up MR images on an annual basis or more frequently as dictated by symptoms.…”
Section: Presentationmentioning
confidence: 99%
“…Specifically, regarding the issue of pain, Magge et al 26 noted that there does not appear to be any correlation between syrinx size or location and the symptom of pain. Although we did find an overall increased syrinx diameter in the 2 surgical cases, the relevance is unclear given the few cases we have.…”
Section: Presentationmentioning
confidence: 99%
See 2 more Smart Citations
“…When no primary disorder is identified, the syrinx is considered idiopathic. The untreated natural history of idiopathic syringomyelia is excellent, 158,159 and the majority of such cases should not be considered for surgical treatment. Small spinal syringes may be difficult to distinguish from minimal dilations of the central canal of the spinal cord.…”
Section: Chiari and Syringomyeliamentioning
confidence: 99%